A Liouville Type Result for Schrödinger Equation on Half-Spaces - Baiyu Liu (Abstract and Applied Analysis)
We consider a nonlinear Schrödinger equation with a singular potential on half spaces. Using a Hardy-type inequality and the moving plane method, we obtain a Liouville type result for its nonnegative solutions.